Dynamical l-bits and persistent oscillations in Stark many-body localization - Buca, B; Gunawardana, TM (American Physical Society, 2022)
Stark many-body localized (SMBL) systems have been shown both numerically and experimentally to have Bloch many-body oscillations, quantum many-body scars, and fragmentation in the large field tilt limit, but these observations have not been fundamentally understood. We explain and analytically prove all these observations by rigorously perturbatively showing the existence of novel algebraic structures that are exponentially stable in time, which we call dynamical l-bits. In particular, we show that many-body Bloch oscillations persist even at infinite temperature for exponentially long-times using a new type of dynamical algebra and provide a bound on the tilt strength for this non-ergodic transition. We numerically confirm our results by studying the prototypical Stark MBL model of a tilted XXZ spin chain. Our work explains why thermalization was observed in a recent 2D tilted experiment. As dynamical l-bits represent stable, localized, and quantum coherent excitations, our work opens new possibilities for quantum information processing in Stark MBL systems even at high temperature.